Blockchain-based access control mechanism for data traceability - Rongna XIE; Hui LI; Guozhen SHI; Yunchuan GUO; Ming ZHANG; Xiuze DONG (Tongxin xuebao)
To improve the transparency and traceability of access control, a blockchain-based access control mechanism for data traceability and provenance was proposed.The proposed access control policy was transferred to the smart contract and deployed on the blockchain, and the access authorization evaluation was realized by executing the smart contract deployed on the blockchain to ensure the decentralization, transparency and traceability of the access control process.The manner of combining off-chain and on-chain was adopted, the object was stored in off-chain data server, and the object index was generated by the object storage address and hash value, and deployed on the object blockchain.The log of object access authorization and access were recorded in the log blockchain, any misbehavior was immutably recorded.The security analysis show that, the proposed mechanism achieve the properties of decentralization, transparency and traceability while ensuring the privacy of data.